Tenses and Root Verbs - N, Shankaranarayanan (International Research Journal of Tamil, 2022)
Tolkappier does not classify the verb by tense; It is the opinion of many scholars that the department has been classified on the basis. He must have pointed out the time objects if he had classified them on the basis of time. There are many differences of opinion among scholars on the classification of verbs from that time to the present time. The reason for this is that Tolkappiyar did not clearly explain the classification of verbs.This article examines what is the basis of Tolkappiyar's verb classification and why Tolkappiyar did not point out the Tense marker.